Effectiveness of high dose spinal cord stimulation for non‐surgical intractable lumbar radiculopathy ‐ HIDENS Study. Issue 2 (14th November 2021) - Mehta, Vivek; Poply, Kavita; Ahmad, Alia; Lascelles, Joanne; Elyas, Amin; Sharma, Sanskriti; Ganeshan, Balaji; Ellamushi, Habib; Nikolic, Serge
Abstract: Objectives: Spinal cord stimulation (SCS) is being increasingly used in non‐surgical intractable low back pain. This study was designed to evaluate the efficacy of high‐dose (HD) SCS utilizing sub‐perception stimulation with higher frequency and pulse width in non‐surgical predominant low‐back pain population at 12 months. Materials and Methods: A total of 20 patients were recruited (280 screened between March 2017 and July 2018) to undergo percutaneous fluoroscopic‐guided SCS (Medtronic 8 contact standard leads and Restore R IPG), with T8 and T9 midline anatomical parallel placement. Sixteen patients completed 12 months follow‐up (500 Hz frequency, 500 μs pulse width, and 25% pulse density). Differences in patients' clinical outcome (NRS back, NRS leg, ODI, PGIC, and PSQ) and medication usage (MQS) at 1, 3, and 12 months from the baseline were assessed using non‐parametric Wilcoxon paired test. Results: The mean NRS scores for back pain (baseline 7.53) improved significantly at 1, 3, and 12 months; 2.78 ( p < 0.001), 4.45 ( p = 0.002), and 3.85 ( p = 0.002), respectively. The mean NRS score for leg pain (baseline 6.09) improved significantly at 1 and 3 months; 1.86 ( p < 0.001) and 3.13 ( p = 0.010), respectively. Mean NRS for leg pain at 12 months was 3.85 ( p = 0.057). ODI and sleep demonstrated significant improvement as there was consistent improvement in medication particularly opioid usage (MQS) at 12 months. Conclusions: This study demonstrates that anatomical placement of leads with sub‐perception HD stimulation could provide effective pain relief in patients who are not candidates for spinal surgery.